Pneumonia in Patients with Chronic Obstructive Pulmonary Disease - Marcos I. Restrepo, M.D., M.Sc.; Oriol Sibila, M.D., Ph.D.,; Antonio Anzueto, M.D. (Tuberculosis and Respiratory Diseases, 2018)
Chronic obstructive pulmonary disease (COPD) is a frequent comorbid condition associated with increased morbidity and mortality. Pneumonia is the most common infectious disease condition. The purpose of this review is to evaluate the impact of pneumonia in patients with COPD. We will evaluate the epidemiology and factors associated with pneumonia. We are discussing the clinical characteristics of COPD that may favor the development of infections conditions such as pneumonia. Over the last 10 years, there is an increased evidence that COPD patients treated with inhaled corticosteroids are at increased risk to develp pneumonia. We will review the avaialbe information as well as the possible mechanism for this events. We also discuss the impact of influenza and pneumococcal vaccination in the prevention of pneumonia in COPD patients.